Blue-light dependent reactive oxygen species formation by Arabidopsis cryptochrome may define a novel evolutionarily conserved signaling mechanism - Consentino, Laurent (2015)
Cryptochromes are widespread blue-light absorbing flavoproteins with important signaling roles. In plants they mediate de-etiolation, developmental and stress responses resulting from interaction with downstream signaling partners such as transcription factors and components of the proteasome. Recently, it has been shown that Arabidopsis cry1 activation by blue light also results in direct enzymatic conversion of molecular oxygen (O2) to reactive oxygen species (ROS) and hydrogen peroxide (H2O2) in vitro. Here we explored whether direct enzymatic synthesis of ROS by Arabidopsis cry1 can play a physiological role in vivo. ROS formation resulting from cry1 expression was measured by fluorescence assay in insect cell cultures and in Arabidopsis protoplasts from cryptochrome mutant seedlings. Cell death was determined by colorimetric assay. We found that ROS formation results from cry1 activation and induces cell death in insect cell cultures. In plant protoplasts, cryptochrome activation results in rapid increase in ROS formation and cell death. We conclude that ROS formation by cryptochromes may indeed be of physiological relevance and could represent a novel paradigm for cryptochrome signaling.